2017
DOI: 10.3390/ijerph14101230
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Review: Land Cover, Meteorological, and Socioeconomic Determinants of Aedes Mosquito Habitat for Risk Mapping

Abstract: Asian tiger and yellow fever mosquitoes (Aedes albopictus and Ae. aegypti) are global nuisances and are competent vectors for viruses such as Chikungunya (CHIKV), Dengue (DV), and Zika (ZIKV). This review aims to analyze available spatiotemporal distribution models of Aedes mosquitoes and their influential factors. A combination of five sets of 3–5 keywords were used to retrieve all relevant published models. Five electronic search databases were used: PubMed, MEDLINE, EMBASE, Scopus, and Google Scholar throug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
68
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(76 citation statements)
references
References 74 publications
2
68
0
4
Order By: Relevance
“…The authors of Reference [8] have shown that Aedes distributions are currently the widest ever recorded, and are now extensive in all continents, including North America and Europe. Both species have become increasingly capable of exploiting man-made container habitats and human blood meal hosts [9,10], demonstrating their high-level of ecological plasticity and remarkable adaptation to urban settings [11]. The abundance and distribution of Aedes mosquitoes are influenced by climatic, topographic, land use and land cover (LULC) factors [10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors of Reference [8] have shown that Aedes distributions are currently the widest ever recorded, and are now extensive in all continents, including North America and Europe. Both species have become increasingly capable of exploiting man-made container habitats and human blood meal hosts [9,10], demonstrating their high-level of ecological plasticity and remarkable adaptation to urban settings [11]. The abundance and distribution of Aedes mosquitoes are influenced by climatic, topographic, land use and land cover (LULC) factors [10].…”
Section: Introductionmentioning
confidence: 99%
“…Both species have become increasingly capable of exploiting man-made container habitats and human blood meal hosts [9,10], demonstrating their high-level of ecological plasticity and remarkable adaptation to urban settings [11]. The abundance and distribution of Aedes mosquitoes are influenced by climatic, topographic, land use and land cover (LULC) factors [10]. The relationship between entomological indicators of Aedes aegypti abundance and dengue virus infection is not straightforward [12], and it is difficult to identify a minimal entomological threshold for dengue transmission [13].…”
Section: Introductionmentioning
confidence: 99%
“…For example, our regression models showed that the distribution range of Ae. albopictus was predicted by a combination of macro-and microhabitat variables such as muddy water quality ( r 2 =25.40) and developed medium intensity areas ( r 2 =22.44) ( Sallam et al 2017b ). These findings were consistent with other researches, which found a link between Ae.…”
Section: Discussionmentioning
confidence: 99%
“…Regression values, calculated using the PROC REG procedure in SAS 9.4, compose the ecological modeling for WNV and inform the relative effects (positive or negatively associated with disease) and magnitude (weighted values of disease effect) of specific environmental or climatic factors for each specimen group (avian, corvid, equine, or human) submitted for testing. The selection of final explanatory variables was based on overall lowest Akaike information criterion (AIC) values via backward elimination, as this method reduces both model over-fitting and collinearity between variables [35,36]. Data was organized, processed, and visualized using JMP 11.0.0 (SAS Institute, Cary, NC, USA) [27].…”
Section: Methodsmentioning
confidence: 99%